Adverse effects of acrolein, a ubiquitous environmental toxicant, on muscle regeneration and mass. Issue 1 (31st October 2018) - Chen, Huang‐Jen; Wang, Ching‐Chia; Chan, Ding‐Cheng; Chiu, Chen‐Yuan; Yang, Rong‐Sen; Liu, Shing‐Hwa
Abstract: Background: Acrolein is an extremely electrophilic aldehyde. Increased urinary acrolein adducts have been found in type 2 diabetic patients and people with a smoking habit. The increased blood acrolein was shown in patients who received the cancer drug cyclophosphamide. Both diabetes and smoking are risk factors for skeletal muscle wasting or atrophy. Acrolein has been found to induce myotube atrophy in vitro . The in vitro and in vivo effects and mechanisms of acrolein on myogenesis and the in vivo effect of acrolein on muscle wasting still remain unclear. Methods: C2C12 myoblasts were used to assess the effects of low‐dose acrolein (0.125–1 μM) on myogenesis in vitro . Mice were exposed daily to acrolein in distilled water by oral administration (2.5 and 5 mg/kg) for 4 weeks with or without glycerol‐induced muscle injury to investigate the effects of acrolein on muscle wasting and regeneration. Results: Non‐cytotoxic‐concentration acrolein dose dependently inhibited myogenic differentiation in myoblasts (myotube formation inhibition: 0.5 and 1 μM, 66.25% and 46.25% control, respectively, n = 4, P < 0.05). The protein expression for myogenesis‐related signalling molecules (myogenin and phosphorylated Akt: 0.5 and 1 μM, 85.15% and 51.52% control and 62.63% and 56.57% control, respectively, n = 4, P < 0.05) and myosin heavy chain (MHC: 0.5 and 1 μM, 63.64% and 52.53% control, n = 4, P < 0.05) were decreased in acrolein‐treated myoblasts. Over‐expression of the constitutively active form of Akt in myoblasts during differentiation prevented the inhibitory effects of acrolein (1 μM) on myogenesis (MHC and myogenin protein expression: acrolein with or without constitutively active Akt, 64.65% and 105.21% control and 69.14% and 102.02% control, respectively, n = 5, P < 0.05). Oral administration of acrolein for 4 weeks reduced muscle weights (5 mg/kg/day: 65.52% control, n = 6, P < 0.05) and cross‐sectional area of myofibers in soleus muscles (5 mg/kg/day: 79.92% control, n = 6, P < 0.05) with an up‐regulation of atrogin‐1 and a down‐regulation of phosphorylated Akt protein expressions. Acrolein retarded soleus muscle regeneration in a glycerol‐induced muscle regeneration mouse model (5 mg/kg/day: 49.29% control, n = 4, P < 0.05). Acrolein exposure reduced muscle endurance during rotarod fatigue performance in mice with or without glycerol‐induced muscle injury (5 mg/kg/day without glycerol: 30.43% control, n = 4, P < 0.05). Accumulation of acrolein protein adducts could be detected in the soleus muscles of acrolein‐treated mice. Conclusions: Low‐dose acrolein significantly inhibited myogenic differentiation in vitro, which might be through inhibition of Akt signalling. Acrolein induced muscle wasting and retarded muscle regeneration in mice. These results suggest that acrolein may be a risk factor for myogenesis and disease‐related myopathy.